Resíduos Sólidos Urbanos: Diagnóstico no Município de Santo Anastácio | Urban Solid Waste: Diagnosis in the Muncipality of Santo Anastácio - Sampaio, Bruna Dienifer Souza (PEGADA - A Revista da Geografia do Trabalho, 2014)
<!--[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE <![endif]--> Introduction: One of the greatest problems in urban areas to-day is the issue of generation and management of urban solid waste which, in the current system of capitalist production, made worse by consumerism, creates a lot of garbage that is disposed of in landfill sites without a thought for the resultant degradation of the environment. There is also the important role of the worker who collects recyclable material which is left over from sales and discarded by the population. They require better, less precarious, working conditions. Given these issues of the disposal of solid waste and the value and dignity attached to the work of collectors, this research seeks to analyze how the process of production, collection and disposal of waste operates in the municipality of Santo Anastácio / SP and to contribute to the environmental planning and integrated management of urban solid waste in the Water Resources Management Unit of Pontal do Paranapanema. Methodology and Development: The methodology consisted of a review of the literature concerning the various themes that inform the work, the use of questionnaires and interviews with workers and those responsible for the cleaning service and the collectors of recyclable material to obtain information concerning forms of production, treatment and final disposal, and field work at the landfill site to evaluate further the information collected. Final thoughts: Given the actions so far undertaken, we can summarize a preliminary analysis of the situation concerning solid waste in the municipality, with the following results: the lack of selective collection through the period from 1997 to 2012 shows the municipal government’s failure to address the problem of garbage, the lack of public awareness, lack of documents and control of the treatment of solid waste in the municipality. Furthermore, both current and previous landfill sites have experienced various problems, such as workers taking recyclable material directly to landfill and minor explosions of methane gas. Finally, these questions relate to the importance of solid waste to supplement the income of these workers and their families, and the development of as elective collection program for the city to promte conservation and preservation of the environment. <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->